Occupational therapy workshops and social cooperatives – towards a more effective occupational rehabilitation for persons with disabilities - Olszewski, Mikołaj (Research Papers of Wrocław University of Economics, 2018)
The aim of the article is to draw attention to the factors which affect the occupational rehabilitation of participants of vocational therapy workshops, to discuss the role of these workshops in terms of social and occupational rehabilitation of the disabled, and present model solutions which enable the participants of the workshops to enter the labour market. Examples of good practice in the area of occupational rehabilitation in cooperation with the Institute of Vocational Activity (ZAZ) are presented as well as the model of social cooperatives of legal entities as innovative and alternative forms of support for vocational rehabilitation in relation to the ZAZ and Supported Employment Enterprise. The article presents also the opportunities that local government have to support the social cooperatives and the benefits thereof through the application of social clauses
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 510, s. 152-164
Keywords: Occupational Therapy Workshops; social cooperatives; people with disabilities; vocational rehabilitation; vocational activation; warsztaty terapii zajęciowej; spółdzielnie socjalne; osoby z niepełnosprawnością; rehabilitacja zawodowa; aktywizacja zawodowa